Limits of Sequences of Feebly-Type Continuous Functions - Balcerzak Marek (Annales Mathematicae Silesianae, 2020)
We consider the following families of real-valued functions defined on 𝕉2: feebly continuous functions (FC), very feebly continuous functions (VFC), and two-feebly continuous functions (TFC). It is known that the inclusions FC ⊂ VFC ⊂ TFC are proper. We study pointwise and uniform limits of sequences with terms taken from these families.